The complete chloroplast genome of Camellia brevistyla (Hayata) Coh. St. (Theaceae: Ericales) from China based on PacBio and Illumina data - Yin, Xin (Mitochondrial DNA B Resour, 2021)
Camellia brevistyla is an economic plant that can produce high-value edible oil in southern China. Using a combination of PacBio RS and Illumina sequencing platforms, the complete chloroplast genome of C. brevistyla was assembled and annotated. This newly deciphered chloroplast genome was 2,731 bp shorter in the ycf1 gene than the previously published C. brevistyla genome. The phylogenetic analysis fully resolved C. brevistyla in a clade with C. kissii, C. chkeiangoleosa, and C. japonica. The results not only supported the proposal to merge the sections Oleifera and Paracamellia, but also showed the close relationship between them and section Camellia.